2009
DOI: 10.1016/j.exppara.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A cathepsin L-like protease from Strongylus vulgaris: An orthologue of Caenorhabditis elegans CPL-1

Abstract: a b s t r a c tCathespin L-like proteases (CPLs), characterized from a wide range of helminths, are significant in helminth biology. For example, in Caenorhabditis elegans CPL is essential for embryogenesis. Here, we report a cathepsin L-like gene from three species of strongyles that parasitize the horse, and describe the isolation of a cpl gene (Sv-cpl-1) from Strongylus vulgaris, the first such from equine strongyles. It encodes a protein of 354 amino acids with high similarity to other parasitic Strongylid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Cathepsins B and B-like proteases are identified in various species 3 . Cathepsins B-like and L-like cysteine proteases are found in Caenorhabditis elegans 4 , 5 . Similar proteases are also detected in some invertebrates 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Cathepsins B and B-like proteases are identified in various species 3 . Cathepsins B-like and L-like cysteine proteases are found in Caenorhabditis elegans 4 , 5 . Similar proteases are also detected in some invertebrates 6 .…”
Section: Introductionmentioning
confidence: 99%
“…C. elegans cpl-1 mutant embryos showed decreased cell division rate, arrest of morphogenesis and eventual death, and it was shown that Ce-CPL-1 was involved in the degradation of yolk 32 , 40 , which provides the major nutrients for developing embryos. Transgenic expression of the H. contortus cpl-1 or S. vulgaris cpl-1 genes rescued the embryonic lethal phenotype of the C. elegans cpl-1 mutant, supporting their function in embryonic development 41 , 42 . Here, we show that Dd-cpl-1 RNAi embryos of D. destructor shared similar phenotypes with the C. elegans cpl-1 mutant, such as the dramatically slow cell division, abortive morphogenesis and embryonic lethal phenotype.…”
Section: Discussionmentioning
confidence: 79%
“…These were amplified using primers designed to the most conserved regions of the incognita, belongs to a family of proteins that affect a broad range of biological processes, including nutrition, digestion and tissue penetration, and may influence the host-parasite relationship (Neveu et al, 2003;Ultaigh et al, 2009). In plant-parasitic nematodes this enzyme is specifically expressed in the intestinal cells and is associated with food digestion and protein degradation (Hassan et al, 2010;Haegeman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the cpl-1 gene occurred equally in eggs, J2 and females of M. hispanica ; however, Shingles et al (2007) reported that in M. incognita the expression of this gene was slightly lower in mature females. The CPL-1 enzyme, identified in secretions of M. incognita , belongs to a family of proteins that affect a broad range of biological processes, including nutrition, digestion and tissue penetration, and may influence the host–parasite relationship (Neveu et al , 2003; Ultaigh et al , 2009). In plant-parasitic nematodes this enzyme is specifically expressed in the intestinal cells and is associated with food digestion and protein degradation (Hassan et al , 2010; Haegeman et al , 2012).…”
Section: Discussionmentioning
confidence: 99%